(3JMQjQ cJGH GQSWQNS aj LQei GdfjQjf hHYOgeGs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s; (3GQSWQNSs
(3ChdgG (B:s
(3Ef GdbeQ jSJeO GdVhA ef GdTeS s
(3BNQgG (B:s
(3Gdajde eXde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B138 - (3U(B142 :s
(3ajgG QShe gfOSjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B512 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B14 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(3453(13)) s
Keywords: (3Gdadcs